2016
DOI: 10.1186/s12920-016-0186-5
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to incorporating genomic risk assessments into population screening programs: the importance of purpose, context and deliberation

Abstract: BackgroundThe use of an overall risk assessment based on genomic information is consistent with precision medicine. Despite the enthusiasm, there is a need for public engagement on the appropriate use of such emerging technologies in order to frame meaningful evaluations of utility, including the practical implementation and acceptability issues that might emerge. Doing so requires the involvement of the end users of these services, including patients, and sections of the public who are the target group for po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…In North Carolina, USA, insurers have recently declined cover for WGS (although pharmacogenomics testing could be done without WGS), as its utility was considered low. There was also concern about the impact of pharmacogenomics on shared decision-making, similar to the findings from a recent US study which demonstrated the importance of purpose, context and deliberation when incorporating genomic risk assessments into population screening programs (Nicholls et al 2016). This study suggested that members of a target patient population could engage meaningfully about their acceptability and utility of genomic information (Nicholls et al 2016).…”
Section: Comparison With Existing Literaturesupporting
confidence: 64%
See 1 more Smart Citation
“…In North Carolina, USA, insurers have recently declined cover for WGS (although pharmacogenomics testing could be done without WGS), as its utility was considered low. There was also concern about the impact of pharmacogenomics on shared decision-making, similar to the findings from a recent US study which demonstrated the importance of purpose, context and deliberation when incorporating genomic risk assessments into population screening programs (Nicholls et al 2016). This study suggested that members of a target patient population could engage meaningfully about their acceptability and utility of genomic information (Nicholls et al 2016).…”
Section: Comparison With Existing Literaturesupporting
confidence: 64%
“…There was also concern about the impact of pharmacogenomics on shared decision-making, similar to the findings from a recent US study which demonstrated the importance of purpose, context and deliberation when incorporating genomic risk assessments into population screening programs (Nicholls et al 2016). This study suggested that members of a target patient population could engage meaningfully about their acceptability and utility of genomic information (Nicholls et al 2016). In another study, there was limited discussion on how different populations (ethnic differences) might react to their metaboliser status which might lead to exclusion of drug prescribing for that individual (Kaphingst et al 2015).…”
Section: Comparison With Existing Literaturementioning
confidence: 56%
“…In addition to racial and ethnic diversity, other factors can impact awareness of and interest in biomedical research participation, such as religious beliefs, family structure, community setting, stigma, fear, or shame regarding carrier status (Mellon, Gauthier, Cichon, Hammad, & Simon, 2013; Tkatch et al, 2014; Tong et al, 2014; Underhill, Habin, & Shannon, 2017). For example, a person's decision to participate in biomedical research can be influenced by confusion about genetic terminology, research procedures, protections for research participants, or by a lack of knowledge about what to expect (Brothers et al, 2011; Clayton, Halverson, Sathe, & Malin, 2018; Etchegary, 2014; Hull et al, 2008; Laranjo, 2016; Lemke, Wolf, Hebert‐Beirne, & Smith, 2010; Nicholls et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thus it seems unlikely that this approach would gain public approval [5••], and this may prove a barrier to maximising the efficacy and cost-effectiveness of such programmes. It is notable that acceptability is likely to vary depending on both the framing of the purpose for population screening-for example as benefit to patients rather than costeffectiveness [36]-and on the context of both the intervention and the population in question [37].…”
Section: Programme/system Principlesmentioning
confidence: 99%